Public policy for the sustainable industries in Semarang Regency - Ardhiansyah Noer Julana; Gatot Sasongko (Faculty of Social and Political Science, Universitas Airlangga, 2019)
The spatial planning policies had become the mediators for political, social, economic, and environmental relations. This study aims to describe the implementation of public policy from the perspective of Dye theory about a spatial planning for industries in Semarang Regency. The primary data used in this study was from nine informants of nine companies which applied for a location permission license for industrial activities. The secondary data was from the Semarang Public Works Office. The study shows that there were nine investment activity plans for industries in Semarang Regency. Initially, the nine applications were not granted permission from the relevant agencies because they were not in accordance with the provisions of spatial planning. However, after being considered by the government in terms of public policy, the nine companies obtained location permission licenses to utilize the land under certain conditions. Thus, the public policy is essentially designed by the government to guarantee and fulfill the needs of the community to conduct investment activities such as industry. The spatial planning policies had become the mediators for political, social, economic, and environmental relations. Thus, harmonization of political, social, economic and environmental aspects would create sustainable development.